Versatile electronically tunable voltage-mode filter based on simple CMOS OTAs - Torteanchai, Usa; Yutthanaboon, Sathian; Sarsitthithum, Kanok; Kumngern, Montree (My University, 2017)
In this paper, a new versatile electronically controllable voltage-mode biquadratic filter with four inputs and three outputs based on simple CMOS operational transconductance amplifiers (OTAs) is presented. By appropriately selecting the input and output terminals, the proposed filter can work as either a single-input multiple-output (SIMO) or a multiple-input single-output (MISO) biquadratic filter without changing the circuit topology. When it is a function of SIMO filter, the circuit provides band-pass (BP), low-pass (LP) and band-stop (BS) voltage responses and using grounded capacitors. The all-pass (AP) and high-pass (HP) voltage responses can be obtained using addition and subtraction circuits. Continually, when it is a function of MISO filter, the circuit can realize five standard non-inverting and inverting filtering functions such as LP, BP, HP, BS and AP filters. Both the circuit functions offer an electronic control of the natural frequency through adjusting the bias currents of OTAs. The filters are absent from active and passive component-matching condition and invertingtype input signal requirements for realizing all filtering responses. The passive and active sensitivities are low. The performances of the proposed filter can be confirmed by PSPICE simulation results.
Keywords: Analog signal processing; Operational transconductance amplifier; Voltage-mode filter